Analysis of the trend of mortality by COVID-19 among brazilian doctors (Research, Society and Development, 2020)
Objective: Analyze the epidemiological profile, the spatial pattern and the trend of mortality from coronavirus-2019 among Brazilian physicians. Methods: Ecological study based on secondary mortality data. Mortality rates of doctors for coronavirus-2019 in Brazil in the period from March to July 2020 were calculated. Spatial analysis performed using the Kernel density technique and temporal analysis using the Joinpoint Regression Analysis model. Results: The highest mortality rates in Brazilian doctors due to coronavirus-2019 were among male doctors, aged 70 or over, working in the area of Clinical Medicine and residing in the northern region of the country. Most of the Brazilian states with the highest number of deaths belonged to the Northeast region. The mortality trend highlighted four inflection points, with an increase in the first two periods, a reduction in the third, and a less expressive increase in the fourth period. Males showed a higher mortality trend than females. Conclusion: Coronavirus-2019 infection in Brazilian doctors needs special attention and rapid actions must designed by the competent authorities.